Feedback loop centered on MAF1 reduces blood–brain barrier damage in sepsis-associated encephalopathy - Xuebiao Wei; Wenqiang Jiang; Zhonghua Wang; Yichen Li; Yuanwen Jing; Yongli Han; Linqiang Huang; Shenglong Chen (Cellular & Molecular Biology Letters)
Abstract Background A previous study found that MAF1 homolog, a negative regulator of RNA polymerase III (MAF1), protects the blood–brain barrier (BBB) in sepsis-associated encephalopathy (SAE); however, the related molecular mechanisms remain unclear. Subjects and methods In this study, a rat sepsis model was constructed using the cecum ligation and puncture (CLP) method. In vitro, rat brain microvascular endothelial cells and astrocytes were stimulated with serum from the sepsis model rats. The loss of MAF1 protein levels and the molecular mechanisms leading to cell damage were investigated. Results It was shown in the SAE models that MAF1 was expressed at low levels. Knockdown of Cullin 2 (CUL2) stimulated the accumulation of MAF1 protein, attenuated the RNA sensor RIG-I/interferon regulatory factor 3 (IRF3) signaling pathway, and reduced cell apoptosis. Furthermore, it increased phosphatase and tensin homolog (PTEN) expression and inactivated the serine/threonine kinase (AKT)/mechanistic target of the rapamycin kinase (mTOR) signaling pathway. Interference with forkhead box O1 (FOXO1) inhibited MAF1 expression and activated the RIG-I/IRF3 signaling pathway, while MAF1 overexpression promoted PTEN expression, decreased cell apoptosis, and normalized autophagy. Conclusions These findings demonstrate that CUL2 promoted MAF1 ubiquitination and caused BBB injury in SAE. Through the regulatory loop of PTEN/AKT/FOXO1/MAF1, CUL2 initiated the gradual downregulation of MAF1, which subsequently regulated polymerase III (Pol III)-dependent transcription and played essential roles in cell apoptosis in SAE. Clinical trial number: not applicable. Graphical Abstract